Effect of periodontal treatment on preclinical Alzheimer's disease—Results of a trial emulation approach - Schwahn, Christian; Frenzel, Stefan; Holtfreter, Birte; Van der Auwera, Sandra; Pink, Christiane; Bülow, Robin; Friedrich, Nele; Völzke, Henry; Biffar, Reiner; Kocher, Thomas; Grabe, Hans Jörgen (Alzheimer's & dementia, 2022)
Introduction We investigated the relationship between periodontal treatment and pre‐clinical Alzheimer's disease (AD). Methods In this quasi‐experimental design, 177 periodontally treated patients from the “Greifswald Approach to Individualized Medicine” cohort, which used the same protocols as the population‐based Study of Health in Pomerania TREND (SHIP‐TREND), and 409 untreated subjects from SHIP‐TREND were analyzed. Subjects were younger than 60 years at the magnetic resonance imaging examination, with a median observation period of 7.3 years. Imaging markers for brain atrophy in late‐onset AD and brain aging were used as the outcomes. Results Robust to sensitivity analyses, periodontal treatment had a favorable effect on AD‐related brain atrophy (–0.41; 95% confidence interval: –0.70 to –0.12; P = .0051), which corresponds to a shift from the 50th to the 37th percentile of the outcome distribution. For brain aging, the treatment effect was uncertain. Conclusion Periodontitis is related to pre‐clinical AD in our population.